Compact wide stopband microstrip lowpass filter using polygon patches and meandered lines - Adel Musavy; Akram Sheikhi (International Journal of Informatics and Communication Technology (IJ-ICT), 2020)
In this paper, a low pass ﬁlter based on T-Shaped resonator is presented. The T-Shaped resonator consists of meandered lines and rectangular patches. Also, the LC model and transfer function of the proposed resonator is presented. For suppression of spurious harmonics, a bandstop structure consists of hexangular patches and open stubs has been utilized. Finally, the wide stopband microstrip lowpass filter with cutoff frequency 2.72 GHz has been simulated, fabricated and measured. The LPF has good characteristics such as wide stopband and insertion loss lower than 0.18 dB in the passband region. The rejection level is less than -20 dB from 2.98 up to 21.3 GHz. The filter size is 10.5 mm×12.7 mm, or 0.131 λg× 0.158 λg, where λg is the guided wavelength. The measured and simulated results of the filter is in good agreement with each other, which show the merits of low insertion loss and wide stopband.